CONCENTRIC-ZONAL AGGREGATE OF REE MINERALS IN FELDSPAR PEGMATITE OF THE VISHNEVYE MOUNTAINS, SOUTH URALS - V.A. Popov (Минералогия)
A concentric-zonal texture of mineral aggregate observed in alkali pegmatite of the Vishnevye Mountains was formed as a result of melt-fluid crystallization in a closed system. At the first stage, rare large monazite crystals were crystallized creating wave concentration fields. Allanite-(Ce), bastnäsite-(Ce), chevkinite-(Ce), thoroaeschinite, apatite-(CaF), zircon, calcite and other minerals crystallized in the end of the monazite growth. Feldspars (syntactic intergrowths of albite with Kfeldspar) were dominant in the final stage of crystallization. The change in the composition of meltfluid (magma) from phosphate-silicate to silicate is atypical.